Analisis guru dan siswa terhadap implementasi kurikulum merdeka belajar di Indonesia - Al-Furqany, Mirza Aulia (Maliki Interdisciplinary Journal, 2024)
One of the factors that has become a factor in changing the curriculum in Indonesia is the very rapid development of science and technology. Because of this technological development, the Freedom to learn curriculum was born, where this curriculum adapts to the current era. But in practice there are still many complicated things about educational institutions in Indonesia. This is evidenced by the implementation of the independent learning curriculum itself. In this case the role of teachers and parents is very important in children’s education, in fact the implementation of the independent learning curriculum has not been implemented in several schools in Indonesia because many teachers find it difficult and confused about the independent curriculum. This can affect the educational process of students at school. Even though progress towards teaching and learning activities depends on good developments in the implementation of the curriculum.